(untitled) (Kinesiology, 2022)
The imposition of COVID-19 lockdown restricted the daily activities of many people, including athletes. This study investigated the training practices of athletes in the Philippines during the early COVID-19 lockdown. A total of 442 athletes answered an online survey (May-July 2020), with questions pertaining to training practices, such as training frequency and duration. Data were analyzed according to: athlete classification (world-class, international, national, state, or recreational), sport category (individual or team), and sex (male or female). During lockdown, significant reductions in training frequency (except recreational, i.e., lower pre-lockdown training) and duration were observed for all athletic classifications. Similarly, training frequency and duration decreased significantly irrespective of sport category and sex. World class athletes appeared to be less affected by lockdown (types of exercise and specific training) as compared to lower classification athletes. Athletes grouped in accordance with sex and sport category demonstrated little to no difference in training practices during the COVID-19 lockdown. The findings of the current study highlight the challenges experienced by athletes during lockdown, which may aid policy makers in the development of guidelines related to lockdown or lockdown-like situations to establish appropriate support for affected athletes. Key words: movement restriction, home training, remote training, sports training, SARS-CoV-2